An Analysis of Improving English Skills of Nursing Students Facing Mbkm (Merdeka Belajar Kampus Merdeka) - Iin Noviana; Shanti Rosmaharani; Pepin Nahariani (MultiTech Publisher, 2023)
Communication is the process of sending thoughts, messages and information. Learning English in Indonesia tends to be taught and studied as a foreign language. The program of Merdeka Belajar (Independent Learning) will provide students to compete in the world of college, and have the opportunity to explore knowledge. This research was conducted on 83 students of STIKES Pemkab Jombang Nursing Bachelor Program, semester 4. The research results are in the form of data which is then analyzed in qualitative descriptive form. The results of the research discuss the implementation of MBKM which includes 2 things, they are student interest in the MBKM program and the benefits felt by students participating in the MBKM program. The conclusion of the study is MBKM activity which is provided meaningful learning for students to understand activities that can be done outside of college, students not only do learning in class but can do activities that can develop their abilities both in class and outside classroom.